2020
DOI: 10.3390/f11090912
|View full text |Cite
|
Sign up to set email alerts
|

Key Techniques for Somatic Embryogenesis and Plant Regeneration of Pinus koraiensis

Abstract: Korean pine is the dominant species of Korean pine forests. It is an economically valuable species that yields oil, high-quality timber and nuts, and it offers great prospects for further development. Complete regenerated plants of Korean pine were obtained via somatic embryogenesis using megagametophytes as the explant. The seeds of 27 families of Korean pine were collected to induce embryogenic lines. We compared the effects of explant collection time, family and medium components (concentrations of sucrose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Moreover, the highest percentage of embryogenic cell lines was obtained at these lower temperatures as compared to 28 • C. Earlier, Montálban et al [75] demonstrated that cold storage of cones for over 1 month increases SE initiation frequency. On the other hand, Gao et al [76] proved that the success of the induction step in some pine species is also dependent on the family origin and collection date of explants. Open-pollinated cones of three families with explants were collected from June to July 2015.…”
Section: Explants and Initiation Of Sementioning
confidence: 99%
“…Moreover, the highest percentage of embryogenic cell lines was obtained at these lower temperatures as compared to 28 • C. Earlier, Montálban et al [75] demonstrated that cold storage of cones for over 1 month increases SE initiation frequency. On the other hand, Gao et al [76] proved that the success of the induction step in some pine species is also dependent on the family origin and collection date of explants. Open-pollinated cones of three families with explants were collected from June to July 2015.…”
Section: Explants and Initiation Of Sementioning
confidence: 99%
“…Here, too, the origin of responses to different temperatures in SE in conifers will have to be analyzed [110]. The effects of the timing of sample collection, its family components, and the means of induction of embryogenic lines have now been successfully demonstrated [111]. It is a challenge for researchers to permanently question all solutions that might seem definitively adopted only a short time ago.…”
Section: Breeding Programs and Biotechnological Alternativesmentioning
confidence: 99%
“…Somatic embriogenesis has been shown to be very successful in other genera of the Pinaceae family: Abies, Larix, Picea, Pinus, and Pseudotsuga, and others of the families Cupressaceae, Taxaceae, Cephalotaxaceae, and Araucariaceae [68,120]. Currently, SE has been achieved for almost 30 pine species [111].…”
Section: Breeding Programs and Biotechnological Alternativesmentioning
confidence: 99%
“…Somatic embryogenesis (SE) is a technique used by plants to reproduce bipolar structures from somatic cells [59]. It entails the co-ordination of four steps: the production of embryogenic lines, proliferation, maturation, and plant regeneration (Figure 1) [60]. This approach serves as a significant experimental model for studying the processes of plant embryogenesis and is also one of the best methods for mass multiplication of elite or genetically modified plants [61].…”
Section: Somatic Embryogenesismentioning
confidence: 99%